TEACHER’S ABILITY IN PREPARING LESSON PLANS FOR ENGLISH AS A FOREIGN LANGUAGE DURING THE PANDEMIC IN THE SENIOR HIGH SCHOOL - Asari, Rahayu Kusuma Widya; Tantra, Dewa Komang; Agustini, Dewa Ayu Eka (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
There are still many students who do not follow online learning well. Students who are not focused on online learning. In addition, there are still many teachers who find it challenging to design appropriate learning for students. This will have an impact on learning activities that cannot run optimally, especially in English subjects. The negative impact of this is that the ability of students will decrease. This study aims to analyze the teacher's ability to prepare EFL lesson plans through Google Classroom, the teacher's obstacles in compiling EFL lesson plans through Google Classroom, and students' obstacles in learning English as a foreign language (EFL) through Google Classroom. The method used in this study is a mixed-method. The method used to collect data is observation, interviews, and questionnaires. The instrument used to collect data is a questionnaire. Before data collection, the three instruments were validated and tested empirically. The technique used to analyze the data is descriptive qualitative and quantitative statistics. The results showed that the ability of teachers to prepare EFL lesson plans through Google Classroom was still lacking. In addition, EFL students also encounter obstacles in learning English as a foreign language (EFL) through Google Classroom.